Insects identified by unqualified scientists: multiple “new” records from the Murmansk oblast of Russia are dismissed as false - Kozlov, Mikhail V (Severnyj (Arktičeskij) federalʹnyj universitet imeni M.V. Lomonosova, 2022)
A recently published book authored by six botanists (Rak NS, Goncharova OA, Poloskova EY, Litvinova SV, Zotova OE, Lipponen IN. 2018. Bioecological analysis of introducents of the family Rosaceae Juss. Kola Science Centre, Apatity, 87 pp.) reports information on 19 species of insects that are declared to damage woody Rosaceae plants in the central part of the Murmansk oblast of Russia. Examination of photographs published in this book revealed that 15 of these 19 species were identified incorrectly and that several of the illustrated species are unlikely to damage woody Rosaceae plants. The most striking examples are errors in determination at the order level: a syrphid fly (Diptera) identified as a leafcutter bee (Hymenoptera), and a sawfly (Hymenoptera) identified as a psyllid (Hemiptera). I provide correct identifications of the insects illustrated in the cited book in order to prevent the spread of erroneous information across future publications and databases.